Radiation cross-linked carboxymethylated starch and iron removal capacity in aqueous solution - Pant, Bhoj Raj; Jeon, Hye-Jin; Song, Hyun Hoon (Macromolecular research, 2011)
Cross-linked carboxymethylated starch derivatives were synthesized and tested for their iron adsorbing capacity in aqueous solutions. To obtain the highly substituted carboxymethyl starch (CMS), a multi-step carboxymethylation process was adopted. The CMS with DS = 0.92 in aqueous medium was then exposed to electron beam radiation (EB) at various doses to yield the cross-linked carboxymethyl starch (CCMS). The CCMS of maximum gel content (87.1%) was obtained at 50 kGy with a 50% (w/v) aqueous CMS solution. The iron removal capacity of the CCMS was almost independent of the pH of the metal solution in the acidic range (pH 3–5), where the physical entrapment of the ion is dominant over a chelation reaction. The high physical entrapment was apparently associated with the high cross-link density. The adsorption capacity improved when the pH approached neutral but the iron showed complete precipitation at pH 7.